Almost sure convergence of recursive kernel estimatiors of the density and the regression under η− weak dependence. Issue 17 (9th August 2021) - Kenza Assia, Mezhoud
Abstract: The result of this work addresses the consistency of recursive kernel estimates of the regression and density functions. We provide almost sure convergence under η − weak dependence using exponential inequality adapted to this context of dependence. Rates of convergence are derived also.